1979
DOI: 10.1172/jci109512
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Memory of Pancreatic B and A2 Cells

Abstract: A B S T R A C T The influence of previous exposure to glucose on the subsequent B-and A2-cell secretory responses to arginine was investigated in the perfused pancreas of the rat. Arginine (8 mM) was administered in two brief (9 min) pulses separated by a period of 66 min. In pancreata from 18-h-fasted animals the two pulses of arginine elicited biphasic glucagon secretory responses, while stimulation of insulin release was barely detectable. When 27.7 mM glucose was administered for 30 min during the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…However, pancreastatin significantly increased (p < 0.05) the enhanced insulin response to a second pulse of 16.7 mM glucose. These results agree with the time-dependent potentiation or memory of the B cell response by glucose as described in literature 1~ 13,14 and suggests a role for pancreastatin in the adaptation of the B cell to glucose stimulation of insulin secretion. As expected 1, pancreastatin did not modify the rate of insulin secretion when the glucose concentration of the perfusion medium was 2.7 mM, showing a lack of effect on non-stimulated insulin release.…”
Section: Resultssupporting
confidence: 92%
“…However, pancreastatin significantly increased (p < 0.05) the enhanced insulin response to a second pulse of 16.7 mM glucose. These results agree with the time-dependent potentiation or memory of the B cell response by glucose as described in literature 1~ 13,14 and suggests a role for pancreastatin in the adaptation of the B cell to glucose stimulation of insulin secretion. As expected 1, pancreastatin did not modify the rate of insulin secretion when the glucose concentration of the perfusion medium was 2.7 mM, showing a lack of effect on non-stimulated insulin release.…”
Section: Resultssupporting
confidence: 92%
“…It is well established that prior exposure to glucose sensitizes the endocrine pancreas to a subsequent glucose stimulus [3][4][5][6][7]. This 'memory' for a previous glucose stimulation was shown to be both time and dosedependently.…”
Section: Insulin Secretion From Pancreatic Beta Cells Is Regulated Bymentioning
confidence: 99%
“…This 'memory' for a previous glucose stimulation was shown to be both time and dosedependently. It was observed in several species, including man [3][4][5][6][7][8][9][10], and there is no evidence that the islet memory described for glucose is due to the release of intestinal peptides and subsequent effects on the beta cell.…”
Section: Insulin Secretion From Pancreatic Beta Cells Is Regulated Bymentioning
confidence: 99%
“…It is an attractive thought that the calcium-lowering effect of glucose described by Hellman et al could be responsible for the reduced insulin response during time-dependent inhibition; this hypothesis has not yet been tested. We demonstrated that inhibition of glucose metabolism with mannoheptulose blocked time-dependent potentiation, whereas suppressors of insulin release, such as adrenaline, somatostatin or diazoxide had no effect [34,38,39,65]. We concluded therefore that metabolism of glucose was necessary for time-dependent potentiation.…”
Section: The Physiology Of Insulin Secretionmentioning
confidence: 87%
“…Although the t 89 of time-dependent inhibition is not known precisely, it is definitely of the order of several minutes and quite different from that of acute stimulus-secretion coupling [33][34][35]. 3The third event, slower in onset, amplifies the insulin response with time, and thus is responsible for the late increase in the secretion rate [36][37][38][39]. We have named this phenomenon time-dependent potentiation; its t 89 is also quite long.…”
Section: The Physiology Of Insulin Secretionmentioning
confidence: 99%